Answer:
[tex]\displaystyle a = \frac{1}{3} \text{ and } b = \frac{2}{3}[/tex]
Step-by-step explanation:
We can use the definition of inverse functions. Recall that if two functions, f and g are inverses, then:
[tex]\displaystyle f(g(x)) = g(f(x)) = x[/tex]
So, we can let j be the inverse function of h.
Function h is given by:
[tex]\displaystyle h(x) = y = 3x-2[/tex]
Find its inverse. Flip variables:
[tex]x = 3y - 2[/tex]
Solve for y. Add:
[tex]\displaystyle x + 2 = 3y[/tex]
Hence:
[tex]\displaystyle h^{-1}(x) = j(x) = \frac{x+2}{3} = \frac{1}{3} x + \frac{2}{3}[/tex]
Therefore, a = 1/3 and b = 2/3.
We can verify our solution:
[tex]\displaystyle \begin{aligned} h(j(x)) &= h\left( \frac{1}{3} x + \frac{2}{3}\right) \\ \\ &= 3\left(\frac{1}{3}x + \frac{2}{3}\right) -2 \\ \\ &= (x + 2) -2 \\ \\ &= x \end{aligned}[/tex]
And:
[tex]\displaystyle \begin{aligned} j(h(x)) &= j\left(3x-2\right) \\ \\ &= \frac{1}{3}\left( 3x-2\right)+\frac{2}{3} \\ \\ &=\left( x- \frac{2}{3}\right) + \frac{2}{3} \\ \\ &= x \stackrel{\checkmark}{=} x\end{aligned}[/tex]